Genetically engineered M2-like macrophage-derived exosomes for P. gingivalis-suppressed cementum regeneration: From mechanism to therapy - Xin Huang; Yifei Deng; Junhong Xiao; Huiyi Wang; Qiudong Yang; Zhengguo Cao (Bioactive Materials, 2024)
Cementum, a thin layer of mineralized tissue covering tooth root surface, is recognized as the golden standard in periodontal regeneration. However, current efforts mainly focus on alveolar bone regeneration rather than cementum regeneration, and rarely take Porphyromonas gingivalis (Pg), the keystone pathogen responsible for periodontal tissue destruction, into consideration. Though M2 macrophage-derived exosomes (M2-EXO) show promise in tissue regeneration, the exosome-producing M2 macrophages are induced by exogenous cytokines with transitory and unstable effects, restricting the regeneration potential of M2-EXO. Here, exosomes derived from genetically engineered M2-like macrophages are constructed by silencing of casein kinase 2 interacting protein-1 (Ckip-1), a versatile player involved in various biological processes. Ckip-1 silencing is proved to be an effective gene regulation strategy to obtain permanent M2-like macrophages with mineralization-promoting effect. Further, exosomes derived from Ckip-1-silenced macrophages (sh-Ckip-1-EXO) rescue Pg-suppressed cementoblast mineralization and cementogenesis. Mechanismly, sh-Ckip-1-EXO delivers Let-7f-5p targeting and silencing Ckip-1, a negative regulator also for cementum formation and cementoblast mineralization. More deeply, downregulation of Ckip-1 in cementoblasts by exosomal Let-7f-5p activates PGC-1α-dependent mitochondrial biogenesis. In all, this study provides a new strategy of genetically engineered M2-like macrophage-derived exosomes for cementum regeneration under Pg-dominated inflammation.